Metagenomes, metatranscriptomes and microbiomes of naturally decomposing deadwood - Tláskal, Vojtěch; Brabcová, Vendula; Větrovský, Tomáš; López-Mondéjar, Rubén; Monteiro, Lummy Maria Oliveira; Saraiva, João Pedro; da Rocha, Ulisses Nunes; Baldrian, Petr (Scientific data, 2021)
Deadwood represents significant carbon (C) stock in a temperate forests. Its decomposition and C mobilization is accomplished by decomposer microorganisms - fungi and bacteria - who also supply the foodweb of commensalist microbes. Due to the ecosystem-level importance of deadwood habitat as a C and nutrient stock with significant nitrogen fixation, the deadwood microbiome composition and function are critical to understanding the microbial processes related to its decomposition. We present a comprehensive suite of data packages obtained through environmental DNA and RNA sequencing from natural deadwood. Data provide a complex picture of the composition and function of microbiome on decomposing trunks of European beech (Fagus sylvatica L.) in a natural forest. Packages include deadwood metagenomes, metatranscriptomes, sequences of total RNA, bacterial genomes resolved from metagenomic data and the 16S rRNA gene and ITS2 metabarcoding markers to characterize the bacterial and fungal communities. This project will be of use to microbiologists, environmental biologists and biogeochemists interested in the microbial processes associated with the transformation of recalcitrant plant biomass.
Keywords: taxonomické DNA čárové kódování; stromy; Fungi; metagenom; Ecosystem; RNA, Ribosomal, 16S; Forests; mikrobiota; dřevo; Česká republika; Fagus; Trees; Bacteria; houby; Microbiota; DNA Barcoding, Taxonomic; mezerníky ribozomální DNA; Wood; Czech Republic; Metagenome; ekosystém; RNA ribozomální 16S; DNA, Ribosomal Spacer; lesy; buk (rod)